A new species of Racelda Signoret, with taxonomical notes and a key to the males of the genus (Hemiptera, Reduviidae, Ectrichodiinae, Ectrichodiini) - Gil-Santana, Hélcio R.; Oliveira, Jader [UNESP] (Pensoft Publishers, 2022)
Racelda ottoi Oliveira & Gil-Santana, sp. nov., belonging to the tribe Ectrichodiini in the subfamily Ectrichodiinae, is described based on males from northeastern Brazil. Photographs of the male types of Racelda alternans Signoret, 1863, R. moerens Breddin, 1898, and R. spurca (Stål, 1860) are presented. A summary of and notes on the taxonomic history of the genus and a key to males are provided.
Keywords: Heteroptera; male genitalia; Neotropics; Pseudoracelda; Racelda aberlenci; Racelda robusta